Development of Microstrip Yagi Antenna for 4G Application - Yip, J.H. (Institute of Electrical and Electronics Engineers Inc., 2021)
In wireless technology, microstrip Yagi antenna is one of the recent technologies that are used to obtain an efficient performance of the antenna. This paper provides a simulation and design works and prototype fabrication of Microstrip Yagi antenna for 4G communication applications. The microstrip Yagi antenna have limitation of having a narrow impedance bandwidth which is not suitable for wide bandwidth applications. In this project a technique for bandwidth enhancement and obtaining a good return loss are studied. The expectation of design had obtained a wider bandwidth and a higher gain with an operating frequency range within 4G Long-Term Evolution (LTE) frequency band. Several parametric studies of the proposed configuration were carried out to characterize the antennas and to verify the simulation result. The final result produces a good return loss and bandwidth which operates at frequency of 2.67 GHz with impedance bandwidth of 0.27 GHz. The antenna is fabricated, and the performance of the antenna is tested and measured. The result shows a closed agreement with simulated result. Â© 2021 IEEE.